Ichthyoplankton and juvenile fishes of a Malaysian river - John, Akhbar; Mohamed, Rozihan; Hossain, Sanower (Noor Publishing, 2017)
The book describes the checklist of Ichthyoplankton and juvenile fishes inhabiting in a tropical river system in Malaysia. We followed recent techniques in molecular identification to accurately identify morphologically cryptic and undifferentiated life stages of fishes collected from Kuantan river, Pahang, Malaysia. As this sampling area is recently (in 2014) experienced severe flood, and the sampling was carried out to investigate post flood effect on fish distribution, the data presented in this book will be instrumental for various comparative studies with other tropical and temperate rivers in the world.